2018
DOI: 10.1159/000494457
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Health Practitioners in Indonesia: Their Profile, Practice and Treatment Characteristics

Abstract: Background: The demand for traditional health care is rising. The study aims to investigate the profile, practice and treatment characteristics of traditional health practitioners who participated in the Indonesia Family Life Survey (IFLS-5) in 2015. Methods: A national community facility cross-sectional survey was carried out with a probability sample of 4,461 traditional health practitioners in Indonesia. Results: Traditional health practitioners were typically female, over 50 years old, had no or lower leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…5, Table 8). Few studies also reported women dominance in the traditional medicine industry [87,88]. However, unique scenarios occur where men become dominant in the traditional medicine market surveys due to religious and cultural reasons.…”
Section: Discussionmentioning
confidence: 99%
“…5, Table 8). Few studies also reported women dominance in the traditional medicine industry [87,88]. However, unique scenarios occur where men become dominant in the traditional medicine market surveys due to religious and cultural reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a previous study in Germany,6 this study found that the use of the traditional practitioner decreased with age. One reason for this could be the large proportion of massages administered to babies and small children by traditional practitioners in Indonesia 7,24. However, the use of traditional medicines did not change with age in this study.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common types of treatment provided by traditional health practitioners in Indonesia was found to be massage for babies (71.4%) 7. In a small study of 91 children (6–18 years old) who were admitted to hospital in Indonesia, 39.6% had used Indonesian herbal medicine prior to admission 8.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional governance practices bars young women practitioners who are still nursing babies, actively breastfeeds or still undergo menstruation ( Figure 5, Table 7). Few studies also reported women dominance in the tradition medicine industry [88,89]. However, unique scenarios occur where men become dominant in the traditional medicine market surveys due to religious and cultural reasons.…”
Section: Discussionmentioning
confidence: 99%